2009
DOI: 10.1016/j.actbio.2008.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of strontium-substituted apatite by solid titration

Abstract: Solid titration was used to explore the solubility isotherms of partially (Srx-HAp, x=1, 5, 10, 40, 60 mol.%) and fully substituted strontium hydroxyapatite (Sr-HAp). Solubility increased with increasing strontium content. No phase other than strontium-substituted HAp, corresponding to the original titrant, was detected in the solid present at equilibrium; in particular, dicalcium hydrogen phosphate was not detected at low pH. The increase in solubility with strontium content is interpreted as a destabilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 38 publications
12
118
3
2
Order By: Relevance
“…This substitution can occur naturally in our daily acidic food consumption with the presence of strontium [19,42] or be induced in dental calcified tissues [15,21] or synthesized [20,43,44] in various strontium/calcium ratios. Synthesized strontium apatite has been reported to demonstrate higher solubility than hydroxyapatite, and the solubility increases with greater strontium substitution (strontium ratio) [43,44]. However, it has also been reported that the dissolution rate of synthetic hydroxyapatite can be retarded in the presence of strontium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This substitution can occur naturally in our daily acidic food consumption with the presence of strontium [19,42] or be induced in dental calcified tissues [15,21] or synthesized [20,43,44] in various strontium/calcium ratios. Synthesized strontium apatite has been reported to demonstrate higher solubility than hydroxyapatite, and the solubility increases with greater strontium substitution (strontium ratio) [43,44]. However, it has also been reported that the dissolution rate of synthetic hydroxyapatite can be retarded in the presence of strontium.…”
Section: Discussionmentioning
confidence: 99%
“…Strontiumapatite can be formed at pH > 7. Pan suggested nucleation of strontium-substituted apatite is easier than biological hydroxyapatite in neutral pH and strontium apatite can work as a template for apatite formation [44]. A work on demineralized enamel showed strontium significantly improved remineralization with fluoride [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors also reported differences in Sr response between lifelong residents and immigrants, suggesting topical and systemic Sr effects. While mechanistic studies [10][11][12] have failed to support earlier epidemiological studies as Sr was shown to enhance apatite solubility as it destabilizes the apatite crystal structure, Srsubstituted apatite was, however, also shown to act as a template for nucleation and to promote apatite growth. 13 Indeed, a very recent in vitro study, 14 investigating remineralization of caries lesions in the presence of Sr and fluoride (F), found not only synergistic Sr+F effects but also an enhancement in lesion remineralization by Sr. An earlier in situ de-/ remineralization study 15 also demonstrated superior anticaries benefits of a Sr-supplemented F dentifrice vs. a F dentifrice control (at identical [F]).…”
Section: Introductionmentioning
confidence: 77%
“…Sr-containing HAp enhanced the proliferation and differentiation of osteoblasts (e.g., MG63) (Capuccini et al, 2008). It also facilitated the nucleation of HAp, therefore, Sr-containing HAp is might be usable as a template for growing new bone (Pan et al, 2009). Zn-containing HAp increases the specific surface area (Tonegawa et al, 2007) and decreases the thermal stability of HAp (Li et al, 2008).…”
Section: Fig 4 Hydroxyapatite Crystalmentioning
confidence: 99%